Emerging Contributions of Cancer/Testis Antigens to Neoplastic Behaviors - Gibbs, Zane A. (Trends Cancer, 2018)
Tumors of nearly every origin activate the expression of genes which is otherwise restricted to gametogenic cells. These genes encode proteins termed cancer/testis (CT) antigens, since expression outside of their naturally immune-privileged site can evoke an immune response. Despite extensive efforts to exploit CT antigens as immunotherapeutic targets, investigation of whether these proteins participate in tumorigenic processes has lagged. Here, we discuss emerging evidence that demonstrates that CT antigens can confer a selective advantage to tumor cells by promoting oncogenic processes or permitting evasion of tumor-suppressive mechanisms. These advances indicate the inherent flexibility of tumor cell regulatory networks to engage aberrantly expressed proteins to promote neoplastic behaviors, which could ultimately present novel therapeutic entry points.